2020
DOI: 10.1039/d0sm01512a
|View full text |Cite
|
Sign up to set email alerts
|

Light-responsive self-assembly of a cationic azobenzene surfactant at high concentration

Abstract: A cationic azobenzene photosurfactant (AzoTAB) forms self-assembled structures with long-range order and optical anisotropy at high concentrations. These high-concentration mesophases are lost or disrupted with UV irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, photocleavage in the surfactant is irreversible, limiting their utilization in industrial applications that require reversible properties. Alternatively, photoswitchable units that undergo structural isomerization upon irradiation are promising building blocks for constructing reversible light-responsive materials. For example, azobenzene moieties have been incorporated into spherical polymer particles that elongate upon exposure to polarized light along the polarization direction. , However, the use of photoswitchable surfactants to tune the shape of BCP particles has never been reported. This is mainly attributed to the difficulty in designing the photoswitchable surfactants that exhibit considerable changes in their amphiphilicity by light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, photocleavage in the surfactant is irreversible, limiting their utilization in industrial applications that require reversible properties. Alternatively, photoswitchable units that undergo structural isomerization upon irradiation are promising building blocks for constructing reversible light-responsive materials. For example, azobenzene moieties have been incorporated into spherical polymer particles that elongate upon exposure to polarized light along the polarization direction. , However, the use of photoswitchable surfactants to tune the shape of BCP particles has never been reported. This is mainly attributed to the difficulty in designing the photoswitchable surfactants that exhibit considerable changes in their amphiphilicity by light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…These isomers display different molecular geometries, electronic absorption spectra, and dipole moments . Azobenzene motifs have been incorporated into surfactant molecules , and studied for their structure–function–assembly relationships. Light-induced switching of a photosurfactant’s conformation ,, and properties has emerged as a powerful strategy for tuning the surfactant’s amphiphilicity on demand …”
Section: Introductionmentioning
confidence: 99%
“…Light-responsive LLC dispersions have previously been created through addition of metallic nanoparticles, which induce photothermal phase changes; , however, the toxicity of nanoparticle additions remains a concern . Alternatively, LLCs can be built from amphiphiles, which contain a photoswitchable group. Of these, azobenzene photosurfactants (AzoPS) have been the most extensively studied . Despite concerns over its potential toxicity, a promising recent work has shown the capability to produce biocompatible azobenzene derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…At higher concentrations, there have been several reports of the self-assembly of AzoPS into higher-order bulk LLC phases using both charged and neutral surfactants; ,,,, however, research has focused on the latter, due to a greater number of hydrogen bonding sites, thought to aid LLC formation . In work by Peng et al , neutral AzoPS molecules, with an oligooxyethylene head and azobenzene-alkyl tail, formed both lamellar and hexagonal LLCs with photoisomerization resulting in a loss of the hexagonal phase. , Houston et al further demonstrated the ability to control LLC phase formation, including lamellar and hexagonal, using the structure, concentration, and temperature in systems of neutral AzoPS, all of which showed loss of LLC order on isomerization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation